PENGARUH HAK KEKAYAAN INTELEKTUAL DAN PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL BAGI PEMBERDAYAAN UMKM - Johnson SMT Pangaribuan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Intellectual Property Rights (IPR) protection plays a crucial role in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, especially in the batik and culinary sectors. Although MSMEs are the backbone of the national economy, many business actors in this sector do not fully understand the importance of IPR or face various obstacles in the registration and enforcement process. This study examines the legal and economic implications of IPR protection for MSMEs, focusing on the challenges faced in registering trademark and copyright rights. Based on a normative legal analysis, this study finds that high costs, complicated procedures, and weak law enforcement are the main barriers for MSME actors in optimally utilizing IPR protection. In addition, the lack of socialization and education regarding IPR also hampers the economic potential that can be obtained from this protection. This study recommends simplifying the registration process, increasing socialization, and strengthening law enforcement to improve the protection and utilization of IPR among MSMEs, especially in the batik and culinary sectors.